World Bank Group Gender Strategy (FY16-23) : Gender Equality, Poverty Reduction and Inclusive Growth - World Bank Group (World Bank, Washington, DC, 2015)
By many measures, 2015 marks a watershed year in the international communitys efforts to advance gender equality. In September, with the adoption of the Sustainable Development Goals (SDGs), UN Member States committed to a renewed and more ambitious framework for development. This agenda, with a deadline of 2030, emphasizes inclusion not just as an end in and of itself but as critical to development effectiveness. At the center of this agenda is the achievement of gender equality and empowerment of all women and girls (SDG 5). In addition to governments, the private sector is increasingly committed to reducing gaps between men and women not just because it is the right thing to do, but because it makes business sense. Gender equality is also central to the World Bank Group’s own goals of ending extreme poverty and boosting shared prosperity in a sustainable manner. No society can develop sustainably without transforming the distribution of opportunities, resources and choices for males and females so that they have equal power to shape their own lives and contribute to their families, communities, and countries. Promoting gender equality is smart development policy.